An opisthographic stele in the Izmir Archaeological Museum - Malay, Hasan; Ricl, Marijana; Chankowski, Andrzej S. (Chiron. Mitteilungen der Kommission für Alte Geschichte und Epigraphik des Deutschen Archäologischen Instituts, 2025)
The article publishes and comments a decree engraved on a stele discovered at Izmir, which can hypothetically be dated to the second century BC. A city of uncertain identity (Smyrna, Ephesus, Priene and Sardis may all be considered candidates) honours the gymnasiarch Aristokrates for the commitment and generosity he demonstrated during his term of office. The procedure for awarding the honours, as well as the nature of the honours, make this decree part of a rich series of documents illustrating the city’s control over the institution of the gymnasium and its internal functioning. The honours (golden crown, bronze statue and painted portrait to be placed in the gymnasium, proclamation of honours during public festivals) were voted on by the ephebes and neoi and then approved by the Council and the People in accordance with the usual procedure. Among the activities of the gymnasium, the decree mentions in particular lectures given for the ephebes by poets and prose writers and provides further evidence that the gymnasium was sometimes open to people of lower social status. As for the interior layout of the gymnasium, the text informs us that it was equipped with a ξηρά, a room used as a dry heat bath.